ANALISIS SEMANTIK PADA ISTILAH-ISTILAH FISIKA YANG BERPOTENSI MENIMBULKAN MISKONSEPSI - Nurul Azizah; Najwa Putri Shalihah; Bunga Sapitri; Cisita Azahra; Rahmansyah (STKIP Subang, 2026)
This study aims to analyze the meaning of physics technical terms that potentially cause misconceptions among students through a semantic approach. The method used is descriptive qualitative with data collected through library research and textual observation of 20 physics technical terms. The analysis was conducted by comparing the meaning of each term based on the Big Indonesian Dictionary (KBBI) and physics textbooks. The results show that differences in meaning between everyday and scientific contexts are the primary factor causing misconceptions, particularly on familiar terms such as force, work, heat, temperature, mass, and momentum, as well as abstract terms such as relativity, quantum, and electromagnetism. This research is expected to assist educators in conveying physics concepts more accurately so that student misconceptions can be minimized from the beginning of learning.